Vibration and handling stability analysis of articulated vehicle with hydraulically interconnected suspension. (July 2019) - Li, Hongxue; Li, Shiwu; Sun, Wencai
Anti-roll hydraulically interconnected suspension (HIS) due to its roll-vibration stiffness and damping performance has been studied and applied in passenger vehicles, buses, and tri-axle straight vehicles. However, very few investigations have been made on six-axle articulated vehicles with the HIS system. Moreover, rollover accidents involving articulated vehicles cause severe casualties, which have attracted wide attention in the vehicle safety field. This calls for a design of a new suspension control technique to improve the handling stability performance at a lower cost and with less energy consumption. This paper presents an anti-roll HIS system control technique to improve the handling stability of a six-axle tractor–semitrailer with nonlinear uncertain parameters. Firstly, the HIS model for leaf-spring suspension of a half semitrailer is established by means of the linear transfer matrix method. Secondly, the power spectral density function is analyzed to validate the obtained model, and equivalent stiffness and damping are computed using natural frequency. Thirdly, six-axle vehicle equations with the HIS model are established considering the equivalent stiffness and damping parameter as the medium. Finally, numerical simulation results are provided and compared with the original vehicle. Dynamic response of the proposed technique is assessed by analyzing roll stability, lateral stability, yaw stability, and articulation stability. The results show that the proposed control technique can effectively improve the handling performance of an articulated vehicle.